2019
DOI: 10.1002/ijc.32496
|View full text |Cite
|
Sign up to set email alerts
|

Targeting ferroptosis in rhabdomyosarcoma cells

Abstract: Recent data suggest that rhabdomyosarcoma (RMS) cells might be vulnerable to oxidative stress‐induced cell death. Here, we show that RMS are susceptible to cell death induced by Erastin, an inhibitor of the glutamate/cystine antiporter xc− that can increase reactive oxygen species (ROS) production via glutathione (GSH) depletion. Prior to cell death, Erastin caused GSH depletion, ROS production and lipid peroxidation. Importantly, pharmacological inhibitors of lipid peroxidation (i.e., Ferrostatin‐1, Liproxsta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 41 publications
1
50
0
Order By: Relevance
“…Activating ferroptosis to eliminate breast cancer cells has emerged as a potential therapeutic approach. Erastin is an inducer of ferroptosis that has been reported to efficiently induce death in various types of cancer cells, such as liver cancer ( 10 ) and rhabdomyosarcoma cells ( 12 ). Consistently, the present study demonstrated that erastin inhibited the viability of breast cancer cells and induced cell death in MCF-7 and MDA-MB-231 cells in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activating ferroptosis to eliminate breast cancer cells has emerged as a potential therapeutic approach. Erastin is an inducer of ferroptosis that has been reported to efficiently induce death in various types of cancer cells, such as liver cancer ( 10 ) and rhabdomyosarcoma cells ( 12 ). Consistently, the present study demonstrated that erastin inhibited the viability of breast cancer cells and induced cell death in MCF-7 and MDA-MB-231 cells in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that ferroptosis is often accompanied by autophagy and can be inhibited by autophagy inhibitors ( 7 9 ). As an inducer of ferroptosis, erastin has been shown to induce ferroptosis in oncogenic RAS mutation cell lines and in other cancer cells, including liver cancer ( 10 ), acute lymphoblastic leukemia ( 11 ) and rhabdomyosarcoma ( 12 ). Although erastin activates ferroptosis in triple-negative breast cancer cells by suppressing the expression of glutathione peroxidase 4 and upregulating the expression of cysteine dioxygenase ( 13 ), understanding is limited regarding the effect of erastin treatment or the mechanism of erastin in other types of breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, up-regulation of ROS production in RMS cells following radiation therapy was rapidly compensated by an up-regulation of nuclear factor erythroid 2-related factor (NRF2) levels which, in turn, promotes the expression of antioxidant enzymes and miRNA that protected RMS cells from ROS-induced DNA damage ( 66 ). This has been suggested as a possible Achilles’ heel of cancer cells, as they may be susceptible to treatments that can alter their redox homeostasis, either by further increasing intracellular ROS levels or by targeting antioxidant abilities ( 64 , 67 ). RMS might be particularly vulnerable to this pathway, as demonstrated by Chen et al using a high-throughput screen.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, carfilzomib and alvocidib, in addition to synthetic statins, where shown to act in synergism with HDAC inhibitors by increasing oxidative stress showing effective activity against ERMS xenografts ( 55 ). Erastin, another GSH-depleting agent that subsequently up-regulates ROS production, also induces RMS cell death ( 67 ). Notably, following ROS-inducing radiation therapy, FPRMS cells were found to produce higher levels of antioxidant miRNA including miR-22 , miR-210 , and miR-375 compared to FNRMS, where the expression of miR-375 was only observed in FPRMS, and certain antioxidant enzymes including catalase and glutathione peroxidase 4 ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, iron chelating agents were able to reverse the accumulation of iron ions caused by the absence of ceruloplasmin, improve the exercise ability of PD mice, and effectively reduce any neurological damage caused by MPTP (Ayton et al, 2013 ), consistent with prior results performed in PD patients (Grolez et al, 2015 ). Do Van et al ( 2016 ) and Dächert et al ( 2020 ) confirmed using in vitro brain slice examination and in vivo MPTP mouse model that PKCα activation caused MEK activation, which, in turn, caused ferroptosis. Therefore, iron chelators, ferrostatin-1, and PKC inhibitors, which regulate ferroptosis, may represent novel drugs for PD patients.…”
Section: Ferroptosis and Nervous System Diseasesmentioning
confidence: 93%